Comparative Analysis of Customer Loyalty in Islamic and Conventional Banks: A Literature Review - Subagiyo, Rokhmat; Djamaluddin, Burhan; Ahsan, Muhamad (al-Uqud : Journal of Islamic Economics, 2020)
This paper aims to analyze customer loyalty to Islamic banks and conventional banks through variables studied from previous research. This study used a qualitative approach to research literature, with data collected from reputable international journal articles indexed Q3 to Q1 and nationally accredited Sinta 3 to Sinta 2. This study examines 55 selected articles about customer loyalty from 1998-2019. The analysis results show that the independent variables, moderating variables, and intervening variables in determining customer loyalty to Islamic banks and conventional banks overlap (have similarities).